Optimal reset unknown input observer design for fault and state estimation in a class of nonlinear uncertain systems. Issue 5 (March 2020) - Hosseini, Iman; Fiacchini, Mirko; Karimaghaee, Paknoush; Khayatian, Alireza
Abstract: This paper proposes a novel kind of Unknown Input Observer (UIO) called Reset Unknown Input Observer (R-UIO) for state and fault estimation of a class of nonlinear uncertain systems using linear matrix inequality (LMI) techniques. In the devised R-UIO, the states of the observer are reset to the after-reset value based on an optimal H ∞ reset law in order to decrease the L 2 norm and settling time of estimation error. It is shown that the utilization of such an observer can significantly improve the transient response of the observer. Moreover, the devised approach can be applied to both SISO and MIMO systems. Furthermore, the robust stability analysis of the devised R-UIO is addressed. Finally, the capabilities of the proposed method are demonstrated by applying it to a Continuous Stirred-Tank Reactor (CSTR) as a practical model.